2014
DOI: 10.1111/bjdp.12028
|View full text |Cite
|
Sign up to set email alerts
|

Are minority status children's cross‐ethnic friendships beneficial in a multiethnic context?

Abstract: Past research has demonstrated the negative impact of perceived ethnic discrimination (PED) on psychological well‐being among children. Given research demonstrating the benefits of cross‐ethnic friendship for children's intergroup attitudes, we examined whether cross‐ethnic friendships would attenuate the effects of PED on well‐being and resilience within a multi‐ethnic context. Two hundred and forty‐seven South Asian British children (M = 11 years) recruited from 37 classrooms completed measures of perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 51 publications
6
82
0
1
Order By: Relevance
“…Hence, affirmation of ideal self may be an effective resource that functions as a protective mechanism supporting resilience in a challenging multiethnic environment where perceived ethnic discrimination and negative stereotypes might have detrimental effects for ethnic minority children, especially for South Asians who often report high levels of ethnic harassment in schools (e.g., Bagci et al, 2014;Eslea & Mukhtar, 2000). The influence of close cross-ethnic friendships via affirmation may be of special advantage that boosts resilience effectively for this ethnic group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, affirmation of ideal self may be an effective resource that functions as a protective mechanism supporting resilience in a challenging multiethnic environment where perceived ethnic discrimination and negative stereotypes might have detrimental effects for ethnic minority children, especially for South Asians who often report high levels of ethnic harassment in schools (e.g., Bagci et al, 2014;Eslea & Mukhtar, 2000). The influence of close cross-ethnic friendships via affirmation may be of special advantage that boosts resilience effectively for this ethnic group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cross-ethnic friendships are related to social competence and skills (Kawabata & Crick, 2008;Lease & Blake, 2005) and decrease intergroup anxiety (Turner et al, 2007). Moreover, previous research has shown that cross-ethnic friendships may buffer the negative effects of perceived ethnic discrimination on psychological well-being (Bagci et al, 2014). Therefore, crossethnic friendships may also foster positive development through decreasing perceived discrimination and intergroup anxiety and increasing social competence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results they obtained generally support the contact hypothesis: intergroup contact is usually negatively related to pronounced prejudices, in both the dominant and the nondominant groups. In addition, cross-ethnic friendships are related to psychological well-being (Bagci, Rutland, Kumashiro, Smith, & Blumberg, 2014;Hui et al, 2015;Mendoza-Denton & Page-Gould, 2008). Berry (2011) has proposed that the choice of an integration strategy is related to a greater number of ethnic minorities or migrants becoming successfully adapted.…”
Section: The Research Hypothesesmentioning
confidence: 99%
“…Research with young adults suggests that cross-ethnic friendships are related to psychological well-being (Mendoza-Denton & Page-Gould, 2008). For children living in multiethnic contexts cross-ethnic friendships have a protective role in psychological well-being (Bagci, Rutland, Kumashiro, Smith, & Blumberg, 2014).…”
mentioning
confidence: 99%